Implementation of a Mental Health Screening Tool at an Adult Homeless Shelter Student-Run Free Clinic in Arizona - Megan Flores; Kelsey Kairis; Steven Ater; Amy Stein; George Chen; Michelle Mifflin (Journal of Student-Run Clinics, 2021)
Background: Mental health conditions are prevalent in people experiencing homelessness. This population may seek care in student-run free clinics (SRFCs), but screening for mental health conditions may not be consistent in this setting. The primary objective of our study was to implement a screening tool and determine the gap in identifying mental health conditions between History and Physical (H&P) examinations and the new screening tool. Secondary objectives were to assess its impact on patient volume and workflow.Methods: Adult patients at a homeless shelter-based SRFC completed a mental health screening survey, separate from acute-care visits, aimed at identifying â€œhigh-riskâ€ mental health conditions using validated questionnaires for identifying domestic violence, alcohol use, depression, anxiety, and mood disorders. Chart review was conducted to identify concordance between patients who screened positive for a high-risk condition using the survey and those with a high-risk condition documented in the acute-care H&P. Visit volume was tabulated and compared between the pre- and post-intervention periods using a t-test. A survey for volunteers was used to gather experiential feedback.Results: Of 354 patients treated at Central Arizona Shelter Services, 123 (34.7%) were evaluated by the research team. Sixty (48.8%) of screened patients were identified as high-risk for at least one mental health condition through the screening tool, and 26 (43.3%) charts were reviewed. Of the patients that were screened as high-risk and reviewed, 15 (57.7%) were not documented as high-risk in the acute-care visit H&P. The clinic volume averaged 11 patients, regardless of whether screening occurred during clinic (p = 0.95). Of clinic volunteers, 191 (97.4%) reported no noticeable impact on clinic operations.Conclusions: The screening survey identified more cases of mental health conditions than the previous standard medical interview. There were no adverse effects on the clinic workflow.